Minimal Surgical Interference with Depomedrol Injection Used to Treated Unicameral Bone Cyst - Jameel, Ahmed K (Diyala Journal of Medicine, 2019)
Background: Simple bone cyst or UCB is a benign tumor of bone mostly in children and young adult treated by different approach. (SBC or UBC) are predilection for the metaphyseal region of the long bones. Our study is to treat UCB cyst by minimal surgical interference with depomedrol injection. Objective: To study the effect of ccuration and depomedrol injection in healing of UCB CYST in short period of time with lest morbidity of the patient. Patients and Methods: Twenty four patients their age between 8 to 30 years (23 cases of long bone including 13 upper humerus and 10 femur), one case is in calcaneus bone treated under GA under fluoroscopic technique and depomedrol injection in local. Results: In 6-8 weeks follow up of the patient after our procedure the processes of healing of UCB cyst almost fully in most of the cases ,the suc.cessfull rate was 98-100% in most of the cases in both clinical picture and radiological picture Conclusion:Find from this study that UCB cyst can be treated successfully by this procedure whatever the age of the patient and the size of the cyst and location.